Implementation of ‘MEDLs’: regional guidelines for management of medical emergencies - Emma Jenkins; Charlotte Ainscough; Marc George; Alexa Jarvis; Tasneem Hosanee; Jim Down; Simon O'Callaghan (Future Healthcare Journal)
Introduction: The fragmented landscape of emergency medical guidelines across individual Trusts has resulted in inefficiencies in accessibility, maintenance and real-time applicability. Clinicians often struggle to locate relevant, up-to-date information quickly in critical situations, leading to potential delays in patient care and clinical decision-making. The absence of a centralised, user-friendly resource contributes to inefficiencies and risks to patient safety.1,2To address this, we developed the Medical Emergency Document Library (MEDL), a regional repository of standardised, one-page, evidence-based guidelines adaptable to local populations. This initiative aims to streamline emergency care, enhance decision-making and improve patient outcomes.1 Materials and methods: A preliminary assessment of existing Trust guidelines revealed a lack of standardisation, limited accessibility and outdated protocols. To resolve these issues, we created a library of one-page protocols covering various medical emergencies (Fig 1). The guidelines were designed for brevity, clarity and adherence to evidence-based practices. They were made available on mobile devices and hospital intranets, and linked to Electronic Health Record (EHR) systems to ensure seamless accessibility.Pilot testing was conducted within a single hospital, requiring the establishment of a local governance framework to expedite guideline approvals and of a steering committee to navigate operational challenges. Recognising the benefits of regional guideline standardisation, such as reducing health inequalities and minimising workload, while allowing for local adaptability, we expanded the MEDL to another Trust. By creating a collaborative regional MEDL committee, we shared resources and experience to scale the initiative. This approach enabled organisations to prioritise individual guidelines, allowed resident doctors to drive local quality improvement projects and fostered a sense of ownership among clinicians. Results and discussion: The implementation of MEDL has demonstrated significant clinical and operational benefits. Across two participating Trusts, over 80 MEDL guidelines were created, with more than 22,000 documented uses within 1 year, reflecting high demand for accessible emergency guidelines.Before MEDL implementation, emergency management varied widely, contributing to inconsistencies in patient care. By standardising protocols, MEDL has reduced variability in decision-making, enhanced efficiency and minimised delays in patient management. Senior clinicians and frontline staff have recognised the benefits, leading to the expansion of the initiative to include paediatric emergency guidelines (PEDLs) and regional guidelines, including hypertensive emergencies and maternal medicine.The integration of MEDL into an app-based platform has been particularly impactful. Over 80% of users accessed the guidelines via mobile devices, highlighting strong preference for digital accessibility. User feedback indicated high satisfaction, with clinicians strongly recommending MEDL to their peers as a critical tool for emergency management. Conclusion: The MEDL initiative has successfully addressed challenges in emergency guideline accessibility, standardisation and usability. By fostering regional collaboration and enabling a scalable model, MEDL has improved consistency in emergency medical care, leading to enhanced clinical efficiency and patient safety. Future expansion aims to integrate MEDL into additional Trusts and specialties, ensuring wider access to standardised, high-quality emergency care protocols. This initiative serves as a model for broader NHS-wide implementation, driving sustainable improvements in emergency medicine and patient outcomes.